(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
Lignin, the second most abundant biopolymer on earth, has the potential as a low cost and renewable precursor for carbon fibers. By creating lignin carbon nanofibers for lightweight structural composites for automobiles and functional applications as electromagnetic shields, the value of lignin will be enhanced. Under the Lignoworks Biomaterials and Chemicals Network program, we demonstrated the feasibility of producing carbon nanofibers from softwood Kraft lignin by electrospinning and heat treatment. The morphological, mechanical, and electromagnetic properties of the lignin carbon nanofiber were characterized. Results showed 10 times increase in strength for the lignin random nanofiber mats after carbonization. Alignment of fibers further improved the mechanical strength. By doping the lignin polymer with carbon nanotubes and functional nanoparticles such as magnetite, we demonstrated the feasibility of translating the strength and electromagnetic function respectively to the lignin nanofiber assemblies. The encouraging results demonstrated the potential of lignin as an engineering material thus establishing a pathway for adding values to the abundantly available lignin.